Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $\alpha + \beta - \gamma = \pi$, and $\sin ^ 2\alpha + \sin^2\beta - \sin^2\gamma = \lambda\sin\alpha\sin\beta\cos\gamma$, then find $\lambda$.

From the first equation we get that $\sin^2\gamma = sin^2(\alpha+\beta) \text{ and } \cos\gamma = -(\alpha+\beta)$.
Putting this in the second equation, we get

$$(2-\lambda)(\tan\alpha\tan\beta - 1) = 0$$
So $\lambda =\boxed{2}$
However, the procedure that I did is very long. Is there a simpler way to solve it?

share|cite|improve this question
up vote 1 down vote accepted

Using Prove $ \sin(A+B)\sin(A-B)=\sin^2A-\sin^2B $


$$\text{As }\sin(\pi-x)=\sin x, \sin^2\beta-\sin^2\gamma=\sin(\alpha)\sin(\beta+\gamma)$$

$$\implies\sin^2\alpha+\sin^2\beta-\sin^2\gamma=\sin^2\alpha+\sin(\alpha)\sin(\beta+\gamma) =\sin\alpha[\sin\alpha+\sin(\beta+\gamma)]$$


$$\text{Finally, }\sin(\beta+\gamma)+\sin(\beta-\gamma)=?$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.